Epstein-Barr virus-specific T-cell response in pediatric liver transplant recipients: a cross-sectional study by multiparametric flow cytometry - Cuesta-Martín de la Cámara, Ricardo; Torices-Pajares, Andrea; Miguel-Berenguel, Laura; Reche-Yebra, Keren; Frauca-Remacha, Esteban; Hierro-Llanillo, Loreto; Muñoz-Bartolo, Gema; Lledín-Barbacho, María Dolores; Gutiérrez-Arroyo, Almudena; Martínez-Feito, Ana; López-Granados, Eduardo; Sánchez-Zapardiel, Elena (Frontiers in Immunology, 2024)
Background. Epstein-Barr virus (EBV) specific T-cell response measurement can help adjust immunosuppression in transplant patients with persistent infections. We aim to define T-cell responses against EBV in a cohort of pediatric liver-transplant patients. Methods. Thirty-eight immunosuppressed pediatric liver-transplant patients (IP) and 25 EBV-seropositive healthy-adult controls (HC) were included in our cross-sectional study. Based on their EBV serological (S) and viral load (VL) status, patients were categorized into IP-SNEG, IP-SPOSVLNEG and IP-SPOSVLPOS groups. T-cell response was assessed at two timepoints by stimulating cells with EBV peptides (PepTivator®) and performing intracellular-cytokine and activation-induced marker staining. Background subtraction was used to determine EBV-specific T-lymphocyte frequency. Results. Polyfunctional CD8+ T cells indicated previous EBV contact (IP-SNEG 0.00% vs IP-SPOS 0.04% and HC 0.02%; p=0.001 and p=0.01, respectively). Polyfunctional CD8+CD107a+IFNɣ+IL2-TNFα- profile was increased in serology-positive (IP-SNEG 0.01% vs IP-SPOS 0.13% and HC 0.03%; p=0.01 and p=0.50, respectively) and viral-load positive (IP-SPOSVLPOS 0.43% vs IP-SPOSVLNEG 0.07% and HC 0.03%; p=0.03 and p=0.001, respectively) patients. Central-memory cells were increased among serology-positive adults (IP-SNEG 0.00% vs IP-SPOS 0.13% and HC 4.33%; p=0.58 and p=0.002, respectively). At the second timepoint, IP-SNEG patients remained negative (first visit 0.01% vs second visit 0.00%, p=0.44). On the other hand, IP-SPOSVLPOS patients had cleared viral loads and, subsequently, decreased polyfunctional CD8+CD107a+IFNɣ+IL2-TNFα- cells (first visit 0.43% vs second visit 0.10%, p=0.81). Conclusion. Polyfunctional CD8+ EBV-specific T-cell response allows detecting EBV previous contact in liver-transplant children. %CD8+CD107a+IFNɣ+IL2-TNFα- is increased in patients with positive viral loads. Central memory CD4+ T-cell population more effectively determines prior EBV-exposure in adults.